Examining the correlation between referee physical fitness, in-game performance metrics, and team dynamics in the Chinese super league. - Fei Zhou; Wei Zhang; Kongyun Huang; Yujie Jiang; Changjing Zhou (PLoS ONE)
This study investigates the relationship between referees' physical fitness, their in-game performance, and team dynamics in the Chinese Super League (CSL). The sample comprised 173 matches from the 2021 CSL season, involving 30 referees (mean age 41 years). The Pearson product-moment correlation coefficient was used to analyze the correlation between referees' physical fitness tests and their match performance indicator, as well as the referee's game performance and the home and away teams' game performance. Key findings include a significant positive correlation between referees' RSAVARIATION and the average speed during home possession (r =  0.16, p =  0.04). Additionally, RASBEST and RASAVERAGE were found to have small to moderate negative correlations with the referees' total distance, average speed, and high-intensity activities during games (r =  -0.20 to -0.34, p < 0.001). Furthermore, significant positive correlations were observed between referees' match performance metrics and the physical outputs of both home and away teams. These findings provide valuable insights for enhancing the understanding of factors influencing referee performance and can inform referee training, testing, and selection processes.